Identification of producer enteroendocrine cells of glucagon like-peptide-1 (GLP-1) in the intestine of alpaca - Hidalgo P., César (2015)
The aim of this study was to immunolocalize the distribution of producer enteroendocrine cells of glucagon-like peptide (GLP-1) on the epithelial intestine of alpacas. A total of 36 young (0-45 days old) and adult alpacas were used and distributed in seven age groups. The intestinal samples were processed by immunohistochemistry using an anti-GLP-1 monoclonal antibody. Positive cells were counted in 15 crypt-villus axis of each intestinal portion in each animal. In the group of newborns, the jejunum was the portion containing more L-cells, while other groups are in the jejunum and ileum. Regarding location, the duodenum showed a sustained increase of L-cells from day 8. The largest number of L cells in the jejunum and ileum occurred in the age groups of 0 and 8-45 days of age, respectively, while in the cecum and colon was observed in the group of adult animals. It is concluded that L-cells in alpacas are present from birth, mainly in the jejunum and ileum.